Fluctuating Hearing Loss in the Only Hearing Ear: Cochlear Implantation in the Contralateral Deaf Side. (20th March 2018) - Russo, Francesca Yoshie; De Seta, Daniele; Lahlou, Ghizlene; Borel, Stéphanie; Nguyen, Yann; Bouccara, Didier; Sterkers, Olivier; Bernardeschi, Daniele; Mosnier, Isabelle
Abstract : Objective: To investigate the hearing performance of adult patients presenting unilateral deafness with contralateral fluctuating hearing loss who received a cochlear implant on the deaf side. Study Design: Case series with chart review. Setting: University tertiary referral center. Subjects and Methods: Preoperatively and at 6 and 12 months postoperatively, 23 patients underwent pure tone audiometry and speech audiometry with disyllabic and monosyllabic words in a quiet environment and sentences in quiet and noisy (signal‐to‐noise ratio +10 dB SPL) environments under best‐aided conditions. The Abbreviated Profile of Hearing Aid Benefit (APHAB) inventory was evaluated preoperatively and at 6 and 12 months postoperatively. Results: No difference was found between pre‐ and postoperative tests for disyllabic and monosyllabic words. For sentences in quiet and noisy environments, a difference between pre‐ and postoperative performance was present at 1 year ( P =. 002 and P =. 02, respectively). In a noisy environment, a difference was present at 6 and 12 months postoperatively as compared with the preoperative value (mean ± SD: 6 months: 42% ± 7.1% vs 61% ± 6.5%, P =. 016). A significant improvement in the APHAB score was found at 6 and 12 months postimplantation (Friedman's 2‐way analysis of variance by ranks, P <. 001). The number of years of hearing deprivation of the deaf ear was not correlated with performance. Conclusion: When incapacitating fluctuating hearing loss occurs in patients presenting a contralateral deaf ear, a cochlear implant is indicated in the latter ear, significantly improving performance in noisy conditions and allowing a better quality of communication to be achieved.